IMPLEMENTATION OF THE MINISTER OF HOME AFFAIRS REGULATION NO. 20/2018 ON THE REPORTING AND ACCOUNTABILITY OF APBDESA IN THE PAGADEN VILLAGE HEAD'S OFFICE - Feling Alissia; Putri Oktaviana Lestari; Dhea Rizkinie Putri; Icih Icih (STIESA Press, 2023)
The Pagaden Village Head Office is an office where the village head, village officials and the community carry out administrative activities in rural pagaden, the administrative process or administration in the pagaden village head office is reporting information, recording information, and making data reports to support the implementation of village government activities, including reporting and accountability of the Village Budget (APBDesa) financial statements. Thus, this report was compiled to find out whether the financial statements made by the pagaden village office have implemented the Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management using 2022 data. The data collection technique uses the interview method with the finance department, and observation of village financial reports made by the finance department of the pagaden village office. The data collected will be analyzed for indicators that match the research criteria and presented in the form of a Likert scale table using a qualitative descriptive method. The results showed that the pagaden village head's office was appropriate in implementing the Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management in the reporting and accountability section, although there were still shortcomings in implementing these regulations such as not being on time in submitting reports on the implementation of the APBDESA to the sub-district and there were several financial reports that were not made by the pagaden village head's office.